Elastic, Optical and Thermal Properties of Teo2-Zno and Teo2-Zno-Alf3 Glass Systems - Shaharuddin, Rosmawati (2008)
This thesis presents the study of binary zinc tellurite, TeO2-ZnO and ternary oxyfluorotellurite, TeO2-ZnO-AlF3 glass system which have been prepared using melt quenching technique. The TeO2, ZnO and AlF3 contents have been changed based on their mole fraction. The physical properties were measured and their amorphous nature was confirmed by x-ray diffraction technique. Additional increment of ZnO in binary and ternary glass systems caused the decreasing of ultrasonic velocity. The values of velocity in ternary glass system are higher as compared to the values in binary glass system. Addition of fluorine into TeO2-based glass system resulted the reduction of Te-O-Te linkages due to a gradual transformation of trigonal bipyramid TeO4 (tbp) through TeO3+1 to trigonal pyramid TeO3 which decreasing the connectivity of the tellurite glass former network. Similar pattern in elastic moduli in both glass systems was observed where the values decreased linearly. Both Young’s modulus and bulk modulus were related to the cross-linking density with large influence on the propagation of ultrasonic velocities. All glass samples were found to have high cross-link densities. The values of Poisson’s ratio lie between 0.1 to 0.2. The elastic properties of these glasses are closely related to the strength of glass networks and structures. The refractive index of the TeO2-ZnO glasses was found to increase from 1.99 – 2.07 for mole fraction of 0.10-0.40 ZnO content with an interval of 0.05. The refractive indices for ternary glass system show an increasing trend in all series of glass and varying between 2.01 – 1.76. The behaviour of the refactive index can be explained in either electron density or polarizability of the ions. In this study, the positions of the fundamental absorption edge shift to higher energy (shorter wavelength) with increasing ZnO content in binary tellurite glasses. The shifting of wavelength was related to the amount of production of the non-bridging oxygen (NBO) in TeO2-ZnO glass system and the effect of fluorine ions replacement to the non-bridging oxygen ions in ternary glass system. Experimental data shows that the values of Eopt decreased with increasing content of ZnO for both glass systems where the values of Eopt for binary glass system varied from 2.34 eV to 1.88 eV for indirect allowed transition. The variation of Eopt with glass composition can be explained by suggesting that the non-bridging oxygen ion content increases with increasing ZnO content, shifting the band edge to lower energies and leading to a decrease in the value of Eopt. FTIR spectra revealed broad, weak and strong absorption bands in the investigated range of wavenumbers from 4000 to 400 cm-1 which associated with their corresponding bond modes of vibration and the glass structure. For pure TeO2 glass, the strong absorption band is located at 626 cm-1. The addition of ZnO to TeO2 shifted the major band from 626 cm-1 to the band at around 669 cm-1. AlF3 greatly affects the binary structure of TeO2-ZnO glasses by shifting the absorption bands to the lower wavenumbers. The thermal properties such as thermal expansion coefficient, glass transformation temperature, Tg, acoustic Debye temperature and softening temperature were collected for both glass systems. Generally, the increase of the thermal expansion coefficient in both glass systems might be due to the changes of the coordination number of TeO2 from 4 to 3 and associated with the creation of non-bridging oxygen that caused the decrease in rigidity. Experimental results showed that values for glass transition temperature were closely related to the chemical bond in the system. The decrease in the glass transition temperature, acoustic Debye temperature and softening temperature values implies that number of bridging oxygen group decreases. This is mainly due to the addition of ZnO which weaken the bond between each atom sample (increases the number of NBOs atom). The bond easier to break and hence the Tg of the sample decreased. The fluorine ions tend to break up the strong TeO2 covalent netrwork of the glass by forming ionic, non-bridging M-F bonds, where M is a metal cation.